MULTI-TRACK DIPLOMACY INDONESIA DALAM UPAYA PENINGKATAN EKSPOR KOPI KE AMERIKA TAHUN 2011-2015 - Halifa Haqqi, Reza Maulana Berlian, Christy Damayanti & (Transformasi, 2016)
Coffee is one commodity exports in Indonesia, not only that, Indonesia is also 10 majorcoffee producer in the world. The United States is one of Indonesia's largest export market sharein terms of quantity and economy. Authors using diplomacy and Multi-Track Diplomacy tomeasure effort of increasing coffee export to United States of America 2011-2015. The purposeof this study is to describe the influence of the perpetrators of the coffee business bothgovernment and non-government of Indonesia that is affecting to increasing the numbers ofIndonesian coffee exports sale to the United States in 2011 to 2015. This research uses aqualitative method based on secondary data put on the subject of Indonesian coffee businesspeople of both government and non-governmental organizations. The results of the research ofthe track one or governments : 1. have a role as a regulator in the legislation which serves tomaintain quality standards. 2. The facilitator for the international coffee events as part of thepromotion of Indonesian coffee. 3. The actor or actors coffee business itself both as seller and asa mediator coffee business. In track 2 or non-governmental namely : 1. Businessman coffeefrom Indonesia who sells coffee in the United States. 2. Barista, Q Grader and Roaster as expertin coffee things .3. Non-governmental organizations that have a specialization in the field ofcoffee and play a role in the process of import-export of coffee in Indonesia. By workingtogether the two parties, the interests of the State can be fulfilled, such as maintainingdiplomatic relations among nations following the event, titled coffee, keeping fixed their importexportactivities that can improve the country's foreign exchange. Suggestions from authors toadd data that can be taken directly from the field about the process from coffee to be exportedand enter the US.Key word : Multi-Track Diplomacy, Government, Coffee